2009
DOI: 10.1063/1.3248186
|View full text |Cite
|
Sign up to set email alerts
|

Glass-forming ability enhanced by proper additions of oxygen in a Fe-based bulk metallic glass

Abstract: Effects of oxygen on glass formation in the Fe73Mo3.0C7.0Si3.3B5.0P8.7 bulk metallic glass were studied in detail. Surprisingly, it was found that a critical level of oxygen is effective in enhancing the glass-forming ability of the current Fe-based bulk metallic glass due to the facts that (i) oxygen can increase the crystallization resistance via suppressing the precipitation of the competitive primary phase and (ii) oxygen can stabilize the glass-forming liquid as manifested by the decrease in the liquidus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…A and B are fabricated using pure raw materials and industrial raw materials, respectively, even though they have the same nominal composition. The industrial raw materials contain large amount of impurities, which may become suitable additional elements to cause a more close-packed atomic structure in the liquid phase of alloy, thus increasing the stability of liquid phase and the difficulty for atomic rearrangements [14][15][16] and leading to higher thermal stability of B compared with A. However, a two-stage crystallization process is observed in DSC thermal scan of A.…”
Section: Resultsmentioning
confidence: 99%
“…A and B are fabricated using pure raw materials and industrial raw materials, respectively, even though they have the same nominal composition. The industrial raw materials contain large amount of impurities, which may become suitable additional elements to cause a more close-packed atomic structure in the liquid phase of alloy, thus increasing the stability of liquid phase and the difficulty for atomic rearrangements [14][15][16] and leading to higher thermal stability of B compared with A. However, a two-stage crystallization process is observed in DSC thermal scan of A.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the higher the liquid phase stability and the crystallization resistance, the larger GFA of a system should be [15,16]. Thus, the effects of Ga additions on the GFA can be understood from the above two aspects:…”
Section: Glass Formationmentioning
confidence: 99%
“…Initially, the nonmetal element of oxygen is generally considered as impurities to severely deteriorate the GFA [19,20] and plasticity [21,22] of BMGs. Recently, it was reported that proper doping of oxygen (∼0.1 at.%) can improve the GFA in some Fe- [23] and Zr-based [24] alloys. The results may give constructive implications that some nonmetal elements with extremely minor addition can be considered as a new group of alloying candidates for the improvement of GFA.…”
Section: Introductionmentioning
confidence: 99%